IMPLEMENTASI KEBIJAKAN PENGEMBANGAN KURIKULUM MADRASAH ALIYAH QISMUL’ALY MEDAN - Mesiono Mesiono; Mursal Aziz; Syafaruddin Syafaruddin (Ta'dib, 2019)
This study aims to find out the steps, characteristics, monitoring and evaluating the implementation of the curriculum development policy of Madrasah Aliyah Qismul ‘Aly Al-Washliyah in North Sumatra. This study uses qualitative research methods of policy analysis. The data were gained by means of in-depth interviews, observation, and documentation. The findings of this study are: a) The steps in developing the Aliyah Qismul 'Aly Al-Washliyah madrasah curriculum were in the form of: education policy formulation through the guidance of the Al-Washliyah Education Council, filed in a Decree (SK), then being socialized to the regions and Madrasah Aliyah Qismul 'Aly, b) the characteristics of the implementation of curriculum development policies for Madrasah Aliyah Qismul' Aly include the curriculum of Diniyah Al-Washliyah, Al-Washliyahan subjects and General Imtihan examinations, c) Monitoring and evaluating the implementation of policies for the development of Madrasah Aliyah Qismul curriculum Aly through the assistance of the Al-Washliyah Education Council and assisted by madrasah supervisors pointed by the government. The evaluation was carried out by going down to the region while monitoring all the policy programs must be implemented.